Inquiring into the sustainable tourism village development through the social complexity of adat peoples in digital era - Fadli, Moh; Hadiyantina, Shinta; Cahyandari, Dewi; Liemanto, Airin; Sholehudin, Miftahus (Faculty of Law, University of Muhammadiyah Malang, 2023)
This research aims to inquire into the concept of sustainable tourism development currently taking place in tourism villages in Indonesia, added with the criteria of social complexity of the locals in the digital era. With a qualitative approach, this research obtained samples of the people of Inner Inner Baduy – Banten, Tenganan Pegringsingan – Bali, and Wonokitri – Tengger. Observation, in-depth interviews, and Focus Group Discussion were also performed to gain validated data, which were further analyzed based on SWOT to help formulate the strategies for sustainable tourism village development. The research results indicate that there was disharmony between the policies of the state and the economy of the Adat peoples, cultural exoticism and modernity, economic development, and the culture of adat tourism. Therefore, the process of planning and setting the criteria for sustainable tourism development should take into account the complexity and social diversity. Furthermore, a Plan for Digital Inclusion for adat people needs to be developed. The contribution of this research is expected to help reduce the disharmony of interest in the development of adat tourism villages and bring about the concept of sustainable tourism development to boost the authenticity of adat villages that correspond with their uniqueness in the digital era.